1997
DOI: 10.1575/1912/5707
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen isotopes in chlorophyll and the origin of Eastern Mediterranean sapropels

Abstract: The goals of this thesis were: (1) to establish methods for the determination of nitrogen and carbon isotope ratios in marine particulate and sedimentary chlorophyll derivatives; (2) to establish chlorophyll ()15N and ol3C as proxies for the nitrogen and carbon isotopic composition of marine phytoplankton; and (3) to use chlorophyll nitrogen isotopic ratios to understand the origin of Late Quaternary Eastern Mediterranean sapropels.Techniques are presented for the determination of chlorin nitrogen and carbon i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 144 publications
(314 reference statements)
1
7
0
Order By: Relevance
“…Similar results were obtained by Falk et al (1975), who observed that CPP516 is extremely unstable in organic solvents in the presence of air. Sachs (1997) and Ocampo et al (1999) also observed that CPP516 degrades rapidly under a variety of conditions. Once care is taken to exclude oxygen from extracts, this degradation can be minimized.…”
Section: Sources Of Cyclic Pheophorbides In the Marine Environment-mentioning
confidence: 84%
“…Similar results were obtained by Falk et al (1975), who observed that CPP516 is extremely unstable in organic solvents in the presence of air. Sachs (1997) and Ocampo et al (1999) also observed that CPP516 degrades rapidly under a variety of conditions. Once care is taken to exclude oxygen from extracts, this degradation can be minimized.…”
Section: Sources Of Cyclic Pheophorbides In the Marine Environment-mentioning
confidence: 84%
“…1). These studies have focused mostly on eukaryotic taxa that are dominant in modern marine systems, as well as on terrestrial plants (Sachs, 1997;Kennicutt et al, 1992). measured an average value of e por = 5.1 ± 1.1& (i.e., chlorophyll was $5& depleted in 15 N relative to biomass) in seven species of eukaryotic phytoplankton and one cyanobacterium (Synechococcus sp., order Chroococcales).…”
Section: Introductionmentioning
confidence: 99%
“…Several field observations confirmed changes in δ 15 N during organic matter diagenesis. Sigman et al (1999), working with the sediments from the Southern Ocean, and Sachs (1997) and Sachs and Rapeta (1999), in the sapropels from Mediterranean Sea, found a 2‰-5‰ positive shift in δ 15 N of bulk sediments relative to unaltered organic matter. On the other hand, Altabet et al (1999a) and Pride et al (1999) found no evidence of diagenetic alterations in δ 15 N of preserved organic matter in California borderland basins and in the Gulf of California.…”
Section: Introductionmentioning
confidence: 96%